Metabolic and Physiological Changes in the Roots of Two Oat Cultivars in Response to Complex Saline-Alkali Stress - Gao, Yugang; Jin, Yongling; Guo, Wei; Xue, Yingwen; Yu, Lihe (Frontiers in Plant Science, 2022)
Saline-alkali stress is a major abiotic stress factor in agricultural productivity. Oat (Avena sativa L.) is a saline-alkali tolerant crop species. However, molecular mechanisms of saline-alkali tolerance in oats remain unclear. To understand the physiological and molecular mechanisms underlying seedling saline-alkali tolerance in oats, the phenotypic and metabolic responses of two oat cultivars, Baiyan7 (BY, tolerant cultivar) and Yizhangyan4 (YZY, sensitive cultivar), were characterized under saline-alkali stress conditions. Compared with YZY, BY showed better adaptability to saline-alkali stress. A total of 151 and 96 differential metabolites induced by saline-alkali stress were identified in roots of BY and YZY, respectively. More detailed analyses indicated that enhancements of energy metabolism and accumulations of organic acids were the active strategies of oat roots, in response to complex saline-alkali stress. BY utilized sugars via sugar consumption more effectively, and amino acids strengthened metabolism and up-regulated lignin and may be the positive responses of BY roots to saline-alkali stress, which led to a higher osmotic adjustment of solute concentrations and cell growth. YZY mainly used soluble sugars and flavonoids combined with sugars to form glycosides, as osmotic regulatory substances or antioxidant substances, to cope with saline-alkali stress. The analyses of different metabolites of roots of tolerant and sensitive cultivars provided an important theoretical basis for understanding the mechanisms of saline-alkali tolerance and increased our knowledge of plant metabolism regulation under stress. Meanwhile, some related metabolites, such as proline, betaine, and p-coumaryl alcohol, can also be used as candidates for screening saline-alkali tolerant oat cultivars.